Intrinsic self-repairing polyurea-based conductive elastomer, preparation method and application thereof

CN122832241APending Publication Date: 2026-09-29EASTERN LIAONING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611204161.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-09-29

AI Technical Summary

Technical Problem

然而,现有自修复材料仍面临核心技术瓶颈:动态可逆作用的引入往往以牺牲材料的力学性能为代价,高自修复效率与高力学强度、高韧性之间的权衡难题,始终是限制其规模化实际应用的关键因素

Benefits of technology

1、本申请选用聚丙二醇双(2-氨丙基醚)作为柔性软段原料,其聚醚链段结构赋予材料优异的延展性和低温柔韧性;同时,利用其端氨基与异氰酸酯基团的高反应活性,使聚合反应在室温、干燥氮气氛围下即可顺利完成,无需额外添加催化剂,亦无需高温处理,从根本上避免了传统端羟基聚氨酯体系因催化剂及环境温湿度波动引发的发泡缺陷。因此,本申请制备工艺简单、生产成本低、便于操作和规模化实施,符合绿色化学的发展理念。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122832241A_ABST
    Figure CN122832241A_ABST
Patent Text Reader

Abstract

This application provides an intrinsically self-healing polyurea-based conductive elastomer, its preparation method, and its applications. The method uses polypropylene glycol bis(2-aminopropyl ether) as the soft segment, isophorone diisocyanate as the hard segment, and 4,4'-diaminodiphenyl disulfide and 1,4-cyclohexanedimethylamine as binary chain extenders. The polymerization reaction is carried out in a dry nitrogen environment at room temperature to obtain a polyurea elastomer containing dynamic disulfide bonds and an alicyclic structure. Then, the ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide is introduced into the polyurea elastomer, and the intrinsically self-healing polyurea-based conductive elastomer is obtained by solution casting. The conductive elastomer provided by this application possesses excellent mechanical properties, self-healing properties, ionic conductivity, antibacterial properties, and biocompatibility, making it suitable for flexible wearable sensors, human motion monitoring devices, and health monitoring devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of flexible sensing materials technology, and in particular relates to an intrinsic self-healing polyurea-based conductive elastomer, its preparation method and application. Background Technology

[0002] With the rapid development of flexible electronics, wearable devices, and artificial intelligence, flexible sensors have attracted widespread attention due to their broad application prospects in fields such as human motion monitoring, smart healthcare, and human-computer interaction. Flexible sensor materials used to acquire physiological signals typically need to possess good tensile strength, stable conductivity, and sensitive response to strain or pressure changes. Currently, various polymeric conductive elastomers have been used to construct flexible sensors, but these materials still face many technical bottlenecks in practical applications.

[0003] Self-healing materials, through their own dynamic mechanisms, can spontaneously or under specific external conditions repair their structure and function after suffering mechanical damage, effectively extending their service life. Introducing self-healing design strategies into the field of flexible sensors can not only enrich device functionality and significantly improve operational stability and service life, but also effectively reduce the generation of electronic waste. However, existing self-healing materials still face core technological bottlenecks: the introduction of dynamic reversible action often comes at the cost of sacrificing the material's mechanical properties. The trade-off between high self-healing efficiency and high mechanical strength and toughness remains a key factor limiting their large-scale practical application. Summary of the Invention

[0004] This application is made in view of the above-mentioned issues, and its purpose is to provide a polyurea-based conductive elastomer that has excellent mechanical properties, high efficiency self-healing ability, stable conductivity and good biocompatibility, which is of great significance for promoting the application of flexible sensors in wearable health monitoring, human-computer interaction and other fields.

[0005] The first aspect of this application also provides a method for preparing an intrinsically self-healing polyurea-based conductive elastomer, comprising the following steps: (1) Synthesis of intrinsic self-healing polyurea elastomer (PASU): Polypropylene glycol bis(2-aminopropyl ether) and isocyanate monomers were dissolved in organic solvents. Under a dry nitrogen atmosphere at room temperature, the isocyanate monomer solution was added dropwise to the polypropylene glycol bis(2-aminopropyl ether) solution, and the polymerization reaction was carried out with continuous stirring at room temperature. Subsequently, 4,4'-diaminodiphenyl disulfide and 1,4-cyclohexanedimethylamine were added to the system, and the reaction was continued with stirring to carry out chain extension. After the reaction was completed, the solution was cast and dried to obtain a self-healing polyurea elastomer containing dynamic disulfide bonds. (2) Synthesis of self-healing polyurea-based conductive elastomer (PASU-xIL): The self-healing polyurea elastomer containing dynamic disulfide bonds was dissolved in an organic solvent, and then an ionic liquid was added. The mixture was stirred and mixed evenly at room temperature and under a dry nitrogen atmosphere. After solution casting and drying, the intrinsic self-healing polyurea-based conductive elastomer was obtained.

[0006] In any embodiment, the amount of the ionic liquid added is 5 wt% to 40 wt% of the mass of the self-healing polyurea elastomer containing dynamic disulfide bonds.

[0007] In any embodiment, the polymerization reaction is carried out at room temperature under a dry nitrogen atmosphere for 4 to 12 hours; the chain extension reaction is carried out at room temperature under a dry nitrogen atmosphere for 0.5 to 2 hours.

[0008] In any embodiment, the drying temperature is 50–70°C.

[0009] The second aspect of this application provides an intrinsically self-healing polyurea-based conductive elastomer, obtained using the above-described preparation method.

[0010] In any embodiment, the molar ratio of the isocyanate monomer, polypropylene glycol bis(2-aminopropyl ether), 4,4'-diaminodiphenyl disulfide and 1,4-cyclohexanedimethylamine is (1.5-2.5):(0.8-1.2):(0.3-0.8):(0.3-0.8).

[0011] In any embodiment, the number-average molecular weight of the polypropylene glycol bis(2-aminopropyl ether) is 400–2000 g·mol⁻¹. -1 The isocyanate monomer is isophorone diisocyanate (IPDI); the ionic liquid is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide [EMIM][TFSI].

[0012] In any embodiment, the molar ratio of the cis to trans isomers of the 1,4-cyclohexanedimethylamine is (65:35) to (85:15).

[0013] In any embodiment, the organic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, or N-methylpyrrolidone.

[0014] A third aspect of this application provides the application of an intrinsically self-healing polyurea-based conductive elastomer in the fabrication of flexible wearable sensors, human motion monitoring devices, or health monitoring devices.

[0015] Compared with the prior art, this application has the following beneficial effects: 1. This application selects polypropylene glycol bis(2-aminopropyl ether) as the flexible soft segment raw material. Its polyether segment structure endows the material with excellent ductility and low-temperature flexibility. Simultaneously, utilizing the high reactivity of its terminal amino groups with isocyanate groups, the polymerization reaction can be successfully completed at room temperature under a dry nitrogen atmosphere, without the need for additional catalysts or high-temperature treatment. This fundamentally avoids the foaming defects caused by catalysts and fluctuations in ambient temperature and humidity in traditional hydroxyl-terminated polyurethane systems. Therefore, the preparation process of this application is simple, the production cost is low, it is easy to operate and scale up, and it conforms to the development concept of green chemistry.

[0016] 2. It breaks through the technical bottleneck of balancing self-healing performance and mechanical properties. Through the synergistic effect of the dynamic disulfide bonds provided by APDS and the alicyclic conformation energy dissipation mechanism provided by CHDA, the material achieves simultaneous improvement in strength and ductility while maintaining excellent self-healing ability.

[0017] 3. It possesses both excellent antibacterial properties and biocompatibility. The membrane-breaking effect of the imidazole cation in the ionic liquid enables the material to achieve an inhibition rate of over 99% against both Escherichia coli and Staphylococcus aureus, and it has no significant cytotoxicity to human skin fibroblasts, meeting the safety requirements for wearable devices in long-term contact with human skin.

[0018] 4. Wide range of applications. This material can accurately monitor the movement of multiple joints in the human body and weak physiological signals such as pulse and respiration, as well as accurately identify the movement state. It has broad application prospects in the fields of flexible wearable sensors, human motion monitoring devices, and health monitoring devices. Attached Figure Description

[0019] Figure 1 This is a synthetic route diagram for an intrinsically self-healing polyurea-based conductive elastomer according to this application; Figure 2 The infrared spectra of the intrinsic self-healing polyurea elastomers prepared in Examples 1 to 3 of this application are shown below. Figure 3 The stress-strain curves are for the intrinsic self-healing polyurea-based conductive elastomers prepared in Examples 1 to 3 of this application. Figure 4 The image shows the sensing performance of the intrinsic self-healing polyurea-based conductive elastomer prepared in Example 1 of this application; where a is the relative resistance variation curve under different strain ranges and b is the norm factor variation curve. Figure 5 The image shows the joint sensing signal of the intrinsic self-healing polyurea-based conductive elastomer PASU-10IL sample prepared in Example 1 of this application; where a is the electrical signal response of finger joint bending, b is the electrical signal response of wrist joint bending, c is the electrical signal response of knee joint bending, and d is the electrical signal response of elbow joint bending.

[0020] Figure 6 The intrinsic self-healing polyurea-based conductive elastomer PASU-10IL sample prepared in Example 1 of this application shows the recognition signal diagrams for different motion states; wherein, a) is the electrical signal response diagram for walking and running, b) is the electrical signal response diagram for standing, sitting and lying down, c) is the electrical signal response diagram for different motion states, d) is the accuracy of recognition for walking and running states, e) is the accuracy of recognition for standing, sitting and lying down states, and f) is the accuracy of recognition for different motion states. Figure 7 The diagrams show the self-healing properties of the intrinsic self-healing polyurea-based conductive elastomer PASU-xIL series samples prepared in Examples 1 to 3 of this application; where a is the mechanical self-healing property diagram and b is the electrical self-healing property diagram. Figure 8 The antibacterial properties and biocompatibility of the intrinsic self-healing polyurea-based conductive elastomer PASU-xIL prepared in Examples 1 to 3 are shown in the figure. Detailed Implementation

[0021] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the intrinsic self-healing polyurea-based conductive elastomer, its preparation method, and its applications. However, unnecessary details may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of essentially the same structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of providing a full understanding of this application by those skilled in the art and are not intended to limit the subject matter of the claims.

[0022] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0023] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0024] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0025] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0026] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0027] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0028] In one embodiment of this application, a method for preparing an intrinsically self-healing polyurea-based conductive elastomer is proposed, comprising the following steps: (1) Synthesis of intrinsic self-healing polyurea elastomer (PASU): Polypropylene glycol bis(2-aminopropyl ether) PPG2000 was added to a reaction flask equipped with a standard glass ground glass joint, and anhydrous N,N-dimethylformamide (DMF) was added. The mixture was stirred until the raw materials were completely dissolved. After stirring, anhydrous DMF solution containing isocyanate monomers was added dropwise to the above PPG2000 solution. After the addition was complete, the reaction mixture was stirred continuously at room temperature. Subsequently, 4,4'-diaminodiphenyl disulfide (APDS) and 1,4-cyclohexanedimethylamine (CHDA) were added to the system, and the reaction was continued with stirring. The entire reaction process was carried out at room temperature under a dry nitrogen atmosphere. After the reaction was completed, the resulting polyurea solution was poured into a polytetrafluoroethylene (PTFE) mold using a solution casting method, dried and cured, and the residual solvent DMF was completely removed to finally obtain polyurea elastomer (PASU).

[0029] (2) Synthesis of self-healing polyurea-based conductive elastomer (PASU-xIL): PASU was added to DMF and magnetically stirred until dissolved. Then, the ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide [EMIM][TFSI] was added to the solution, and stirring was continued at room temperature under a dry nitrogen atmosphere to ensure homogeneity. The mixture was then poured into a PTFE mold. The solvent was evaporated by drying to obtain the conductive elastomer.

[0030] In this application, APDS contains dynamic disulfide bonds (-SS-), which can undergo reversible breakage-exchange-rearrangement reactions under thermal stimulation, serving as the core functional unit for achieving the intrinsic self-healing properties of the material. CHDA contains an alicyclic structure, and its cis-trans isomerization transition can bring about efficient energy storage and dissipation effects, helping to improve the ductility and fatigue resistance of the material. The synergistic effect of APDS and CHDA enables the prepared polyurea elastomer to successfully overcome the classic technical challenge of balancing intrinsic self-healing and mechanical properties.

[0031] The introduction of ionic liquids provides the system with three functions: (1) its cations and anions form continuous ion transport channels in the polyurea network, giving the material stable ionic conductivity; (2) the hydrogen bond interaction between the ionic liquid and the polyurea chain segments can effectively regulate the glass transition temperature of the system, enhance the mobility of molecular chain segments, and thus accelerate the self-repair process; (3) imidazole cations have a cationic membrane-breaking effect, giving the material broad-spectrum antibacterial properties. The realization of the above three functions requires the following conditions to be met simultaneously: First, the type of ionic liquid must be matched. Ionic liquids containing imidazole cations must be selected to utilize their cationic membrane-breaking effect to achieve broad-spectrum antibacterial properties. The anions must have weak coordination and large volume characteristics (such as bis(trifluoromethanesulfonyl)imide anions) to ensure ionic conductivity and competitive interaction with the hydrogen bonds of polyurea bonds; Second, the amount added must be between the percolation threshold and the network destruction threshold. When it is below 5 wt%, the ionic liquid is dispersed in islands and cannot build continuous ion channels. The concentration of imidazole cations is insufficient to destroy the bacterial cell membrane, and the plasticizing effect is weak and cannot effectively reduce the glass transition temperature. Temperature, above 40wt%, excessively disrupts the hydrogen-bonded cross-linked network of polyurea, leading to a collapse in mechanical load-bearing capacity and possible phase separation and leakage. Third, the polyurea matrix network structure needs to retain a moderate amount of free volume. The introduction of 1,4-cyclohexanedimethylamine provides insertion space for ionic liquids by disrupting the regular stacking of hard segments. If the matrix cross-linking is too dense, the ionic liquid will have difficulty penetrating uniformly into the hard segment region, limiting both plasticization and the construction of conductive channels. Fourth, the dispersion process needs to ensure uniform distribution at the molecular level, relying on the sufficient dissolution and gentle drying of the aforementioned organic solvents. If the dispersion is uneven, the local enrichment or aggregation of ionic liquids will lead to discontinuous conductive channels, uneven mechanical properties, and antibacterial failure.

[0032] In some embodiments, the amount of the ionic liquid added is 5 wt% to 40 wt% of the mass of the self-healing polyurea elastomer containing dynamic disulfide bonds.

[0033] If the addition amount is less than 5 wt%, the ionic liquid is dispersed in an island-like pattern within the polyurea three-dimensional network, failing to form a continuous ionic conductive pathway, resulting in excessively low conductivity and insufficient sensing sensitivity. Simultaneously, the plasticizing effect is weak, the glass transition temperature decreases only slightly, the molecular chain segment mobility is limited, and the self-healing rate decreases significantly. Furthermore, the imidazole cation concentration is insufficient to effectively disrupt bacterial cell membranes, leading to substandard antibacterial performance. If the addition amount exceeds 40 wt%, the anions and cations in the ionic liquid act as competing ligands for hydrogen bonds, excessively disrupting the urea bond hydrogen bond crosslinking network between polyurea molecular chains. This results in a sharp decrease in physical crosslinking density, significantly reduced tensile strength and modulus, and insufficient material load-bearing capacity. Additionally, excessive ionic liquid may exceed the swelling capacity limit of the polyurea network, leading to phase separation, exudation, or surface stickiness, deteriorating dimensional stability and long-term service reliability. Within this range, the ionic liquid can be uniformly dispersed in the polyurea matrix and form continuous ionic channels, maintaining sufficient mechanical strength and structural integrity while ensuring stable ionic conductivity, excellent self-healing kinetics, and broad-spectrum antibacterial properties.

[0034] In some embodiments, the polymerization reaction takes 4 to 12 hours, and the chain extension reaction takes 0.5 to 2 hours.

[0035] During the polymerization stage, polypropylene glycol bis(2-aminopropyl ether) and isophorone diisocyanate need to be homogeneously mixed at the molecular level and react fully in solution to form a structurally uniform prepolymer with terminal isocyanate groups. If the reaction time is too short, the monomer conversion rate will be insufficient, the prepolymer molecular weight will be too low and widely distributed, and residual soft segments will lead to stoichiometric mismatch in subsequent chain extension reactions, resulting in a significant decrease in the mechanical strength of the material. If the reaction time is too long, the viscosity of the prepolymer will continue to increase, the stirring mass transfer efficiency will decrease, and the terminal isocyanate groups are prone to side reactions with trace amounts of moisture or active hydrogen in urea bonds during long-term storage, leading to uncontrollable crosslinking degree and increased molecular structural defects. During the chain extension stage, 4,4'-diaminodiphenyl disulfide and 1,4-cyclohexanedimethylamine need to react fully with the prepolymer with terminal isocyanate groups to construct urea bond hard segments and achieve microphase separation. If the chain extension time is too short, the reaction between the amino and isocyanate groups will be incomplete, resulting in insufficient hard segment construction, inadequate physical crosslinking density, and negatively impacting mechanical strength and self-healing properties. If the chain extension time is too long, the formed urea bond hard segments may undergo further biuret crosslinking side reactions with residual isocyanate groups, leading to excessive network crosslinking, increased material brittleness, and uncontrolled exchange of dynamic disulfide bonds under continuous shearing, disrupting the network structure's regularity. Within this time range, sufficient prepolymerization and complete chain extension can be ensured, while suppressing side reactions, enabling the controllable synthesis of high molecular weight linear polyurea.

[0036] In some embodiments, the drying temperature is 50–70°C.

[0037] This invention constructs a self-healing polyurea elastomer with excellent comprehensive performance by employing a synergistic strategy of dynamic disulfide bonds and alicyclic chain extenders. The dynamic disulfide bonds provided by APDS are the core driving force for the material's intrinsic self-healing; under thermal stimulation, the disulfide bonds undergo reversible breakage and recombination, allowing the molecular chains at the damaged interface to reconnect. The alicyclic structure provided by CHDA achieves efficient energy dissipation during stretching through a cyclohexane chair-twist boat conformational transformation, endowing the material with excellent ductility and fatigue resistance. The structural differences between the two chain extenders lead to a synergistic enhancement effect: the rigid benzene ring structure of APDS provides high tensile strength, while the alicyclic structure of CHDA endows the molecular chains with superior mobility, optimizing the dispersion of hard segments in the system, thereby improving the material's elongation at break.

[0038] In one embodiment of this application, an intrinsically self-healing polyurea-based conductive elastomer is proposed, which is obtained by the above-described preparation method.

[0039] This invention uses polypropylene glycol bis(2-aminopropyl ether) as the soft segment, endowing the material with excellent ductility and low-temperature flexibility. Isophorone diisocyanate is used as the isocyanate monomer, and 4,4'-diaminodiphenyl disulfide and 1,4-cyclohexanedimethylamine are used as binary chain extenders. Through polymerization, an intrinsically self-healing polyurea elastomer containing dynamic disulfide bonds and an alicyclic structure is obtained. Then, the ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide is introduced into the polyurea matrix, and a polyurea-based conductive elastomer is obtained through solution casting. This invention endows the material with intrinsic self-healing ability through the reversible exchange reaction of dynamic disulfide bonds, while utilizing the alicyclic cis-trans isomerization conformational transformation of 1,4-cyclohexanedimethylamine to achieve efficient energy dissipation. This allows the material to not only maintain excellent room-temperature self-healing ability but also possess high strength and high toughness.

[0040] The design of chain extenders for self-healing polyurea elastomers in existing technologies also has significant limitations. For systems that rely solely on aromatic diamines containing dynamic disulfide bonds (such as 4,4'-diaminodiphenyl disulfide compounds) as a single chain extender, although the dynamic disulfide bonds can endow the material with a certain intrinsic self-healing ability, the rigid aromatic ring structure is prone to excessive aggregation of hard segments, limiting the mobility of molecular chains; moreover, this system lacks an effective energy dissipation mechanism, and stress concentration is difficult to alleviate during deformation, often resulting in high brittleness, low elongation at break, and poor fatigue resistance, making it difficult to meet the requirements of flexible sensors for large deformation and long-term cyclic use. Conversely, if only alicyclic or aliphatic diamines (such as 1,4-cyclohexanedimethylamine compounds) are used as a single chain extender, although the alicyclic structure can provide some flexibility and energy dissipation through conformational changes, the lack of reversible dynamic covalent bonds in the molecular chain means that after mechanical damage, the molecular chains at the fracture interface cannot achieve re-crosslinking through dynamic bond breaking-exchange-rearrangement, thus lacking intrinsic self-healing ability. Simultaneously, due to the lack of the reinforcing effect of the rigid aromatic ring structure, the load-bearing strength of the material is also significantly insufficient. Furthermore, some chain extenders containing active groups such as carboxyl groups (such as 3,5-diaminobenzoic acid) have carboxyl groups with isocyanate groups that are far more reactive than amino groups. The reaction between them is easily accompanied by decarboxylation or amidation side reactions, releasing carbon dioxide gas, leading to foaming defects during polymerization and making it difficult to obtain dense polyurea elastomer films through solution casting. Moreover, these chain extenders also cannot simultaneously provide dynamic reversible bonds and conformational energy dissipation mechanisms. This application overcomes the limitations of existing technologies that rely on a single chain extender or simply replace the type of chain extender, and solves the problem of achieving a balance between intrinsic self-healing, high strength, and high toughness. However, it also has potential risks related to process compatibility and material density.

[0041] In some embodiments, the number-average molecular weight of polypropylene glycol bis(2-aminopropyl ether) is 400–2000 g·mol⁻¹. -1 .

[0042] If the molecular weight is lower than 400 g·mol -1 If the soft segment chain length is too short, it is difficult to form an effective flexible phase region and sufficient molecular chain entanglement, resulting in excessive material rigidity, significantly reduced elongation at break, and loss of elastomer characteristics; if the molecular weight is higher than 2000 g·mol⁻¹, the material will be more rigid. -1 Excessive dilution of the relative content of hard segments and insufficient physical crosslinking density lead to decreased tensile strength and poor dimensional stability. Furthermore, increased viscosity and difficulty in film formation during solution casting, coupled with a reduced segment diffusion coefficient, hinder interdiffusion and self-repair of molecular chains at the damaged interface. This application experimentally verifies that controlling the content within this range allows for the formation of a well-defined microphase separation structure between the soft segments and the urea bond hard segments. This enables the material to maintain excellent ductility and low-temperature flexibility while possessing sufficient mechanical strength, structural stability, self-repair kinetics, and solution processing performance.

[0043] In some embodiments, the isocyanate monomer is isophorone diisocyanate; the molar ratio of the isocyanate monomer, polypropylene glycol bis(2-aminopropyl ether), 4,4'-diaminodiphenyl disulfide and 1,4-cyclohexanedimethylamine is (1.5-2.5):(0.8-1.2):(0.3-0.8):(0.3-0.8).

[0044] Isophorone diisocyanate provides isocyanate groups (-NCO), while polypropylene glycol bis(2-aminopropyl ether), 4,4'-diaminodiphenyl disulfide, and 1,4-cyclohexanedimethylamine provide amino groups (-NH2). The molar ratio of total -NCO to total -NH2 groups must be close to 1:1 to ensure the formation of linear high-molecular-weight polyurea. If the proportion of isophorone diisocyanate is too high, the excessive -NCO groups can lead to over-crosslinking or residual isocyanate, increasing the material's brittleness and reducing its biocompatibility. If the proportion is too low, the polymerization reaction is incomplete, the molecular weight is insufficient, and the mechanical strength is significantly reduced. If the proportion of polypropylene glycol bis(2-aminopropyl ether) is too high, the soft segment content is too large, the hard segment is diluted, the physical crosslinking density is insufficient, the material's load-bearing capacity decreases, and creep is likely to occur. If the proportion is too low, the flexible soft segment phase region is discontinuous, the material's rigidity is too high, the elongation at break is reduced, and it loses its elastomer characteristics. If the proportion of 4,4'-diaminodiphenyl disulfide is too high, the rigid aromatic ring structure becomes excessively aggregated, increasing the material's brittleness. Furthermore, the relative proportion of 1,4'-cyclohexanedimethylamine is compressed, resulting in insufficient energy dissipation mechanisms. If the proportion is too low, the dynamic disulfide bond density is insufficient, significantly reducing the material's intrinsic self-healing ability. If the proportion of 1,4-cyclohexanedimethylamine is too high, the alicyclic structure becomes too dominant, decreasing tensile strength. Additionally, the relative proportion of 4,4'-diaminodiphenyl disulfide is compressed, reducing the dynamic disulfide bond density and decreasing self-healing efficiency. If the proportion is too low, the lack of an alicyclic conformational transformation energy dissipation mechanism significantly reduces the material's ductility and fatigue resistance. Within this proportion range, the components work synergistically, simultaneously satisfying stoichiometric requirements, microphase separation structure construction, and the performance balance of self-healing, high strength, and high toughness.

[0045] In some embodiments, the molar ratio of the cis to trans isomers of the 1,4-cyclohexanedimethylamine is (65:35) to (85:15).

[0046] The cis isomer exhibits a bent configuration with low symmetry, effectively disrupting the regular, tightly packed hard segments and providing space for the chair-to-boat conformational transition of the cyclohexane ring, thus achieving efficient energy storage and dissipation. The trans isomer exhibits a linear configuration with high symmetry, which facilitates the formation of regular hydrogen bonds between hard segments, increasing physical crosslinking density and tensile strength. If the proportion of cis isomers is too high (cis:trans ratio greater than 85:15) and the trans isomer content is too low, the regularity of hard segments is insufficient, the hydrogen bond network is weakened, and the physical crosslinking density decreases significantly, leading to reduced tensile strength and modulus, poorer dimensional stability, and increased susceptibility to creep. If the proportion of cis isomers is too low (cis:trans ratio less than 65:35) and the trans isomer content is too high, the hard segments become excessively regularly packed, the hydrogen bond network is too strong, the material becomes more brittle, the elongation at break decreases, and the conformational transition space of the cyclohexane ring is limited, resulting in reduced energy dissipation efficiency and deteriorated fatigue resistance. Within this ratio range, the cis isomer dominates to ensure energy dissipation and ductility, while retaining an appropriate amount of trans isomers to maintain the physical cross-linking of hard segments and load-bearing strength, thereby achieving synergistic optimization of toughness and strength.

[0047] In some embodiments, the ionic liquid is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide [EMIM][TFSI].

[0048] Ionic liquids in polyurea matrices need to reach a percolation threshold to form continuous ion transport channels, giving the material stable ionic conductivity. At the same time, their anions and cations interact competitively with urea bonds and soft-segment ether oxygen atoms on the polyurea molecular chain to exert a plasticizing effect, reduce the glass transition temperature, and enhance the mobility of molecular chain segments, thereby accelerating the self-healing process. In addition, the membrane-breaking effect of imidazole cations endows the material with broad-spectrum antibacterial properties.

[0049] In some embodiments, the organic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, or N-methylpyrrolidone.

[0050] The solvents mentioned above are all strongly polar aprotic solvents with high dipole moments and high dielectric constants. They can effectively disrupt the strong hydrogen bond network of urea bonds between polyurea molecular chains, allowing the polyurea segments to be fully solvated and extended. This ensures that the polymerization reaction proceeds smoothly in a homogeneous solution, avoiding localized gelation or phase separation. Simultaneously, these solvents have excellent solubility for the ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, promoting the uniform molecular-level dispersion of the ionic liquid in the polyurea matrix and facilitating the subsequent formation of continuous ion transport channels. More importantly, these solvent molecules do not contain active hydrogen groups such as hydroxyl or amino groups, exhibiting chemical stability. Under room temperature polymerization conditions, they will not undergo side reactions with isocyanate groups (-NCO), fundamentally avoiding foaming, chain termination, and stoichiometric mismatch problems caused by solvent participation in the reaction. Furthermore, the boiling points of the aforementioned solvents are in the range of 153–202°C, forming a reasonable gradient with the subsequent drying temperature of 50–70°C. This ensures that the solvent remains stable during the reaction stage to maintain a homogeneous system, while also facilitating complete removal through gentle heating during the drying stage, thus preventing residual solvent from affecting material properties. If protic solvents containing active hydrogen (such as water, alcohols, and amines) are used, the active hydrogen in the solvent molecules will react violently with the isocyanate groups, leading to uncontrolled polymerization, foaming of the material, and deterioration of mechanical properties. If weakly polar aprotic solvents (such as toluene and hexane) are used, they cannot effectively dissolve polyurea and ionic liquids, resulting in phase separation and making homogeneous polymerization and solution casting difficult. If highly volatile solvents (such as diethyl ether and acetone) are used, they evaporate too quickly at room temperature, failing to maintain the stable homogeneous environment required for the polymerization reaction, and easily leading to uneven local concentrations and excessively wide molecular weight distributions.

[0051] Example The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0052] Example 1 A method for preparing an intrinsically self-healing polyurea-based conductive elastomer includes the following steps: S1. Synthesis of intrinsic self-healing polyurea elastomer PASU: In this embodiment, 1 g (1 mmol) of PPG2000 was added to a 100 mL reaction flask equipped with a standard glass ground glass joint, and 10 mL of anhydrous DMF was added. The mixture was stirred until the raw materials were completely dissolved. After stirring for 5 min, 10 mL of anhydrous DMF solution containing 2 mmol of IPDI was added dropwise to the above PPG2000 solution. After the addition was complete, the reaction mixture was stirred continuously at room temperature for 6 h. Subsequently, 1 mmol of APDS and CHDA (cis-trans isomer molar ratio of 75:25) were added to the system, and the reaction was stirred for another 30 min. The entire reaction process was carried out at room temperature under a dry nitrogen atmosphere. After the reaction was completed, the obtained polyurea solution was poured into a PTFE mold using a solution casting method, cured at 60 °C, and the residual solvent DMF was completely removed, finally yielding the self-healing polyurea elastomer PASU.

[0053] In this step, PPG2000, as a flexible soft segment, provides the material with excellent ductility and low-temperature flexibility; IPDI, as an isocyanate monomer, reacts with amino groups to form urea bond hard segments; APDS, as a functional chain extender containing dynamic disulfide bonds, is the core functional unit for achieving the material's intrinsic self-healing properties, and its disulfide bonds can undergo reversible breakage-exchange-rearrangement reactions under thermal stimulation; CHDA, as an alicyclic chain extender, its cis-trans isomerization conformational transformation can bring about an efficient energy dissipation effect, improving the material's ductility and fatigue resistance. The synergistic effect of these two is the key technology in this invention that overcomes the difficulty of simultaneously achieving self-healing and mechanical properties.

[0054] The polymerization reaction is carried out at room temperature without a catalyst, utilizing the high reactivity of amine and isocyanate groups to complete the reaction, thus avoiding foaming defects caused by catalysts and fluctuations in ambient temperature and humidity in polyurethane systems. A reaction time of 6 hours ensures the prepolymerization reaction proceeds fully, and the reaction continues for 30 minutes after the addition of the chain extender to ensure complete chain extension.

[0055] S2. Synthesis of self-healing polyurea-based conductive elastomer PASU-10IL: In this embodiment, 1.8 g of PASU was added to 40 mL of DMF and magnetically stirred until dissolved. Then, 0.2 g of ionic liquid [EMIM][TFSI] was added to the solution, and the mixture was stirred for 30 min at room temperature under a dry nitrogen atmosphere to ensure uniform mixing. The mixture was then poured into a polytetrafluoroethylene mold, and the solvent was evaporated at 60°C to obtain an ionic gel, named PASU-10IL.

[0056] Example 2 A method for preparing an intrinsically self-healing polyurea-based conductive elastomer is the same as step S1 in Example 1, except that: S2. Synthesis of self-healing polyurea-based conductive elastomer PASU-20IL: 1.8 g PASU was added to 40 mL DMF and magnetically stirred until dissolved. Then, 0.4 g of ionic liquid [EMIM][TFSI] was added to the solution, and the mixture was stirred for 30 min at room temperature under a dry nitrogen atmosphere to ensure homogeneity. The mixture was then poured into a polytetrafluoroethylene mold, and the solvent was evaporated at 60 °C to obtain an ionic gel, named PASU-20IL.

[0057] Example 3 A method for preparing an intrinsically self-healing polyurea-based conductive elastomer is the same as step S1 in Example 1, except that: S2. Synthesis of self-healing polyurea-based conductive elastomer PASU-30IL: 1.8 g PASU was added to 40 mL DMF and magnetically stirred until dissolved. Then, 0.6 g of ionic liquid [EMIM][TFSI] was added to the solution, and the mixture was stirred for 30 min at room temperature under a dry nitrogen atmosphere to ensure homogeneity. The mixture was then poured into a polytetrafluoroethylene mold, and the solvent was evaporated at 60 °C to obtain an ionic gel, named PASU-30IL.

[0058] Example 4 A method for preparing an intrinsically self-healing polyurea-based conductive elastomer is the same as steps S1 and S2 in Example 1, except that the molar ratio of APDS to CHDA in step S1 is 0.8:1.2.

[0059] Example 5 A method for preparing an intrinsically self-healing polyurea-based conductive elastomer is the same as steps S1 and S2 in Example 1, except that the molar ratio of APDS to CHDA in step S1 is 1.2:0.8.

[0060] Examples 1-5 of this invention all yielded polyurea-based ionogel conductive elastomers with self-healing properties. The conductive elastomers obtained in Examples 1-3 are used as examples for further research. Specific research methods and results are shown below: The instruments and characterization methods used in this application are as follows: (1) Infrared spectroscopy (FT-IR): The test was performed using a Spectrumho Fourier transform infrared spectrometer from PerkinElmerg, USA. The wavenumber range of the absorption spectrum scan was 500-4000 cm⁻¹. -1 .

[0061] (2) Scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS): The surface morphology of the sample was observed using the Quattro S scanning electron microscope from Thermo Fisher Scientific, and elemental surface scanning analysis was performed in conjunction with EDS.

[0062] (3) Mechanical property testing: The mechanical properties were tested using a CMT6103 electronic universal testing machine from Meters Industrial Systems. The samples were prepared using a dumbbell-shaped polytetrafluoroethylene mold of national standard type I. The tensile rate during the test was 50 mm·min. -1 By plotting stress as the Y-axis and strain as the X-axis, the stress-strain curve of the conductive elastomer can be obtained.

[0063] (4) Sensing performance testing: The tests were conducted using the CHI760E electrochemical workstation from Shanghai Chenhua Instruments Co., Ltd. When testing the conductivity and sensing performance of the conductive elastomer sample, the conductive elastomer was prepared into a 30mm diameter using a polytetrafluoroethylene mold. 15mm The electrode, measuring 3mm in size, is secured at both ends with double-ended alligator clips. The other end of each clip is connected to an electrochemical workstation. The IT mode is selected to record the strain current change of the dual-network conductive elastomer, and the strain sensing signal is represented by the relative resistance change (ΔR / R0). The resistance (R, Ω) is calculated using the following formula:

[0064] In the formula, Voltage (V) applied to the electrochemical workstation. The current (A) of the elastic body.

[0065] The change in relative resistance is calculated using the following formula:

[0066] In the formula, The resistance value of the elastic body when strain is applied. This represents the initial resistance value of the elastomer.

[0067] Flexible sensors assembled from conductive elastomers typically have their sensitivity determined by a gauge factor ( ). The normative factor can be calculated using the following formula, which measures the normative factor.

[0068]

[0069] In the formula This represents the change in relative resistance. The strain applied to the elastic body includes the applied force.

[0070] (5) Self-healing test of mechanical properties: The test was conducted using a CMT6103 electronic universal testing machine from MTES Industrial Systems. After the sample was completely cut with a scalpel, the two cut surfaces were immediately and completely bonded together. The sample was placed at room temperature for a period of time to allow it to self-heal, and then the self-healing efficiency was tested using the universal testing machine. Self-healing efficiency ( It can be calculated using the following formula.

[0071]

[0072] In the formula The fracture strength or elongation at break after self-healing is considered. This represents the breaking strength or elongation at break of the original conductive elastomer.

[0073] (6) Self-healing test of conductivity: The test was conducted using the CHI760E electrochemical workstation from Shanghai Chenhua Instrument Co., Ltd. Both ends of the sample were fixed with double-ended alligator clip electrodes, and the other end of the alligator clip electrodes was connected to the electrochemical workstation. The it mode was selected to record the current change of the elastomer. The sample was completely cut off by an insulated plastic blade. After waiting for a period of time, the cut surfaces were put back together. After the current stabilized, the current recovery time was recorded.

[0074] like Figure 1 As shown, the synthesis of an intrinsic self-healing polyurea-based conductive elastomer of the present invention is divided into two stages: the polymerization reaction of the intrinsic self-healing polyurea elastomer PASU containing dynamic disulfide bonds and alicyclic structures, and the construction of an ionic conductive network induced by ionic liquid.

[0075] First, PASU was obtained by polymerization at room temperature using polypropylene glycol bis(2-aminopropyl ether) (PPG2000) as the flexible soft segment raw material, isophorone diisocyanate (IPDI) as the isocyanate monomer, and 4,4'-diaminodiphenyl disulfide (APDS) and 1,4-cyclohexanedimethylamine (CHDA) as binary chain extenders. The PPG2000 segment, as the flexible soft segment, imparts excellent ductility and low-temperature flexibility to the material; IPDI provides the rigid hard segment, reacting with amino groups to form urea bonds, thus imparting mechanical strength and structural stability to the material; APDS, as a functional chain extender containing dynamic disulfide bonds, allows its disulfide bonds (-SS-) to undergo reversible breakage-exchange-rearrangement reactions under thermal stimulation, serving as the core functional unit for the material's intrinsic self-healing properties; CHDA, as an alicyclic chain extender, allows its cyclohexane structure to achieve efficient energy storage and dissipation through chair-twist boat conformational transformation, imparting excellent ductility and fatigue resistance to the material. The synergistic effect of APDS and CHDA enables the material to achieve simultaneous improvement in both high strength and high toughness while maintaining efficient self-healing capabilities.

[0076] The synergistic effect of APDS and CHDA requires the simultaneous satisfaction of the following control factors: First, the molar ratio of the binary chain extenders must be balanced. The dynamic disulfide bond density provided by APDS and the alicyclic conformational transformation space provided by CHDA must be matched. If the proportion of APDS is too high, the excessive aggregation of rigid aromatic rings leads to excessively strong hard segments and increased brittleness, thus inhibiting the energy-consuming toughening mechanism of CHDA. If the proportion of CHDA is too high, the excessive dilution of dynamic disulfide bond density by alicyclic flexibility results in insufficient self-repair driving force. Second, the order of addition and the reaction process must be controllable step by step. Polypropylene glycol bis(2-aminopropyl ether) and isophorone diisocyanate must be fully prepolymerized to form terminal isocyanate prepolymers before APD is introduced simultaneously. The reaction involves chain extension of S and CHDA to ensure that both chain extenders are statistically embedded into the polyurea backbone, forming a relatively regular block structure. If all raw materials are added simultaneously, the reaction proceeds randomly, resulting in disordered hard and soft segment sequences and disruption of the microphase separation structure. Thirdly, the ratio of hard and soft segments must be appropriate. The molar ratio of isophorone diisocyanate to polypropylene glycol bis(2-aminopropyl ether) must ensure that the volume fraction of hard segments is sufficient to form a physical cross-linked network, while maintaining the continuity of the soft segment phase region to provide a flexible matrix environment for the conformational transformation of CHDA. Fourthly, the reaction temperature must be strictly controlled within room temperature to avoid uncontrolled thermal exchange of dynamic disulfide bonds during polymerization, which could lead to uncontrolled molecular weight distribution and network structure defects. These factors collectively determine whether APDS and CHDA can achieve a complementary distribution of rigid self-healing hard segments and flexible energy-consuming hard segments at the molecular scale, rather than a simple physical blend.

[0077] Secondly, the synthesized PASU was uniformly mixed with the ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide [EMIM][TFSI] in a certain proportion in DMF. After solution casting and solvent evaporation, the intrinsic self-healing polyurea-based conductive elastomer PASU-xIL was obtained. During the film formation process, the ionic liquid was uniformly dispersed in the three-dimensional polyurea network. Its imidazole cations and bis(trifluoromethanesulfonyl)imide anions formed continuous ion transport channels inside the polyurea matrix, endowing the material with stable ionic conductivity. At the same time, the cations and anions in the ionic liquid formed competitive hydrogen bond interactions with the urea bonds and soft segment ether oxygen atoms on the polyurea molecular chain, effectively controlling the glass transition temperature of the system, improving the molecular chain segment mobility, and accelerating the self-healing process. In addition, the imidazole cations endowed the material with broad-spectrum antibacterial properties.

[0078] To fully utilize the properties of ionic liquids, the following key control factors must be met: First, the ionic liquid structure must be compatible with the polyurea matrix. Ionic liquids containing imidazole cations and weakly coordinating bulky anions (such as bis(trifluoromethanesulfonyl)imide) must be selected. The imidazole cations provide antibacterial activity and compete with hydrogen bonds for sites, while the bulky anions ensure the degree of ion pair dissociation and migration rate within the polyurea matrix. Second, solution blending must achieve molecular-level homogeneity. This relies on a strongly polar aprotic solvent to co-dissolve PASU and the ionic liquid, and thorough stirring to ensure the ionic liquid is uniformly dispersed between the polyurea chains in the form of ion pairs or free ions. Inhomogeneous mixing will lead to localized enrichment or aggregation of the ionic liquid, resulting in discontinuous conductive channels and compromised mechanical properties. Third, the polyurea matrix needs to provide sufficient hydrogen bond competing sites. The urea bonds (-NH-CO-NH-) and soft segment ether oxygen atoms (-O-) on the PASU molecular chain are the necessary structural basis for the competitive hydrogen bond interaction between the ionic liquid anions and cations. If the matrix lacks such polar sites, the ionic liquid cannot effectively insert into the polyurea hydrogen bond network, and the plasticizing effect and glass transition temperature regulation effect are lost. Fourth, the solvent removal rate needs to be mild and controllable. The solvent evaporation rate during the drying process must match the diffusion rate of the ionic liquid in the matrix. If the removal is too fast, the ionic liquid will migrate to the surface with the solvent and accumulate, and the ion channels inside the matrix will be broken. If the removal is too slow, the residual solvent will continue to plasticize, resulting in low mechanical properties.

[0079] Under external force, the polyurea covalent backbone provides basic load-bearing capacity, while the multiple hydrogen bond network (hydrogen bonds between urea bonds and between soft segments and ionic liquids) preferentially breaks to dissipate energy. Meanwhile, dynamic disulfide bonds undergo reversible breakage and recombination under thermal stimulation, achieving network structure reconstruction and stress release. When the external force is removed or the crack closes, the molecular chains at the fracture interface re-establish cross-linking points under the synergistic drive of hydrogen bonds and dynamic disulfide bonds. Simultaneously, the ionic liquid rapidly rebuilds continuous ion transport channels, allowing the conductive pathway and mechanical network to recover synchronously. This endows the ionogel conductive elastomer with high strength, high ductility, efficient self-healing ability, and stable ion conductivity. This multi-synergistic mechanism of "covalent cross-linking network + multiple hydrogen bond network + dynamic disulfide bond network + ion conductivity network" is the fundamental reason why the intrinsic self-healing polyurea-based conductive elastomer of this invention differs from existing materials with a single cross-linking system or a single self-healing mechanism, achieving a synergistic breakthrough in mechanical properties and self-healing efficiency, as well as stable ion conduction.

[0080] The realization of multiple synergistic mechanisms requires the following key control factors: First, the cross-linking density of the covalent backbone needs to be appropriate. The polyurea backbone is formed through linear polymerization, avoiding the introduction of irreversible chemical cross-linking points to ensure that the molecular chain segments have the necessary degrees of freedom of movement under stress, providing a structural basis for preferential hydrogen bond breaking and reversible disulfide bond exchange. Second, the multiple hydrogen bond network needs to form a fracture energy level difference. The bond energy difference between strong hydrogen bonds between urea bonds and weak hydrogen bonds between soft segments and ionic liquids needs to be reasonably matched so that weak hydrogen bonds break preferentially under external forces to dissipate energy, while strong hydrogen bonds maintain network integrity, achieving hierarchical energy distribution. Third, the dynamic disulfide bond exchange rate needs to match the hydrogen bond recombination rate. The dynamic disulfide bond breaking-exchange-rearrangement reaction provided by APDS under thermal stimulation needs to be on a similar time scale to the dissociation-recombination kinetics of hydrogen bonds, so as to ensure that hydrogen bonds and disulfide bonds can synergistically drive interface reconstruction after the removal of external force. Fourth, the ionic conductive network needs to be topologically interlocked with the mechanical network. The ionic liquid needs to form penetrating ion channels in the polyurea matrix and entangled with molecular chains, so that the ion channels respond synchronously when the mechanical network is deformed and are synchronously reconstructed when the mechanical network is repaired, rather than being decoupled from each other.

[0081] Figure 2 Infrared spectra of the self-healing polyurea elastomer PASU prepared in Examples 1 to 3, and the intrinsic self-healing polyurea-based conductive elastomer PASU-xIL. The IPDI in the PASU spectrum is at 2260 cm⁻¹. -1 The characteristic -NCO stretching vibration peak at 3310–3350 cm⁻¹ completely disappeared, indicating that the reactive -NCO groups in the reaction system had been completely consumed. Meanwhile, the CHDA / APDS peak at 3310–3350 cm⁻¹... -1 The sharp NH stretching vibration peaks in the region showed a significant decrease in absorption intensity in the PASU spectrum, confirming a reaction between the active hydrogen in the amino group and the NCO group, laying the foundation for the formation of the polymer backbone. A series of new characteristic absorption peaks corresponding to the formation of the polymer backbone clearly appeared in the PASU spectrum: 1635 cm⁻¹ -1 The strong and broad absorption band at 1538 cm⁻¹ can be attributed to the stretching vibration of C=O in -NH₃CO₃NH₃; -1 The absorption peak at 1105 cm⁻¹ is a characteristic peak of the coupling of the NH bending vibration and CN stretching vibration in the urea group, further confirming the successful formation of these two characteristic chemical bonds. Furthermore, the absorption peak at 1105 cm⁻¹... -1 The strong COC stretching vibration peaks originating from PPG2000 were fully preserved. The above infrared spectral characterization results jointly confirm that PASU is a product of the polymerization reaction of IPDI with CHDA / APDS (reacting to form urea hard segments) and PPG2000 (reacting to form polyether soft segments).

[0082] The introduction of ionic liquids (ILs) leads to complex intermolecular interactions within the system: on the one hand, ILs can form hydrogen bonds with PPG segments, effectively enhancing the structural stability of the system; on the other hand, ILs disrupt the original hydrogen bond network between polyurea molecular chains. These two interactions compete and counterbalance each other, fully demonstrating the complexity of the molecular interaction mechanism in this polymer system. With increasing IL content, the system exhibits improved stability at 3100-3200 cm⁻¹. -1 The characteristic peak of stretching vibration of the CH bond on the imidazole ring appears in the region, and also at 1058 cm⁻¹. -1 The characteristic absorption peak of IL was observed. The appearance of the above characteristic peaks confirms that IL has been successfully introduced into the polyurea system and has generated intermolecular interactions with the polyurea backbone.

[0083] Figure 3 The stress-strain curves of the intrinsic self-healing polyurea-based conductive elastomer PASU-xIL prepared in Examples 1 to 3 are shown. As the ionic liquid content increased from 10 wt% to 30 wt%, the tensile strength of the material gradually decreased from 2.8 MPa to 1.15 MPa, and the elongation at break decreased from 2350% to 1678%. This trend stems from the competitive disruption effect of the ionic liquid on the hydrogen bond crosslinking network of the polyurea matrix—the anions and cations in the ionic liquid can act as competitive ligands for hydrogen bonds, interacting with the urea bonds on the polyurea molecular chains, thereby reducing the effective hydrogen bond crosslinking density between molecular chains. Notably, even with an ionic liquid content of 30 wt%, the material still maintains a tensile strength of 1.15 MPa and an elongation at break of 1678%, demonstrating significantly superior overall mechanical properties compared to most currently reported flexible ionogel materials for sensing.

[0084] Figure 4 The sensing performance of the intrinsic self-healing polyurea-based conductive elastomer PASU-10IL prepared in Example 1 is shown in Figure a, where Figure a represents the relative resistance variation curve under different strain ranges, and Figure b represents the normalization factor variation curve. As the strain of the conductive elastomer increases from 100% to 200%, the relative resistance increases from an average of 281% to an average of 700%; as the strain range expands from 0%–100% to 100%–200%, the normalization factor increases from 2.8 to 4.4. This indicates that the sensor still possesses excellent and stable linear sensing response capability over a wide strain range, and can adapt to the sensing and detection needs of all scenarios from small strain to large strain.

[0085] Figure 5The images show the joint sensing signal of the intrinsic self-healing polyurea-based conductive elastomer PASU-10IL sample prepared in Example 1. Figure a shows the electrical signal response of finger joint flexion; figure b shows the electrical signal response of wrist joint flexion; figure c shows the electrical signal response of knee joint flexion; and figure d shows the electrical signal response of elbow joint flexion. The results indicate that this flexible sensor exhibits excellent sensitivity to finger joint flexion at different angles, accurately capturing subtle changes in the joint flexion angle (a). Simultaneously, for cyclic flexion movements of the wrist, elbow, and knee joints (bd), the sensor also demonstrates good dynamic response consistency and maintains stable sensing output during long-term cyclic testing, without significant signal attenuation or drift.

[0086] Figure 6 The image shows the recognition signal diagrams of the intrinsic self-healing polyurea-based conductive elastomer PASU-10IL sample prepared in Example 1 of this invention for different motion states. Figure a shows the electrical signals for walking and running. The results indicate that the sensor can clearly capture the dynamic changes in plantar pressure under these two motion states: compared to normal walking, the contact frequency between the human foot and the ground is faster and the instantaneous pressure is greater during running. Correspondingly, the resistance change signal output by the sensor exhibits a higher frequency and a more significant amplitude. The signal characteristics of the two motion states are significantly different, enabling effective differentiation and recognition of the two dynamic motion modes with an accuracy rate of 97.5% (Figure d). Figure b shows the electrical signals for standing, sitting, and lying down. The results show a significant positive correlation between the sensor's electrical signal response amplitude and the pressure load on the sole of the foot under these three static postures: In the lying position, the pressure exerted by the foot on the insole is minimal, corresponding to the lowest resistance change amplitude of the sensor; in the sitting position, the foot pressure is at a moderate level, and the sensor resistance change amplitude is also in the middle range; while in the standing position, the entire body weight is concentrated on the foot, resulting in maximum foot pressure, and the corresponding sensor resistance change amplitude also reaches its peak. The sensor signal characteristics for the three static postures differ significantly, enabling accurate and stable differentiation of different static body postures, with a 100% discrimination rate (Figure e). Figure c shows the electrical signals for different motion states. The results show that the sensor can accurately capture subtle differences in foot pressure under four fine motion states. Combined with deep learning algorithms, the recognition accuracy for the four fine motion states is 96.25%.

[0087] Figure 7Figure 1 shows the self-healing performance of the intrinsic self-healing polyurea-based conductive elastomer PASU-xIL series samples prepared in Examples 1 to 3. Figure 2a shows the mechanical self-healing performance. When the ionic liquid content increases from 0 wt% to 30 wt%, the mechanical repair efficiency of the dual-network conductive elastomer samples remains at an excellent level of over 90%, and the repair efficiency gradually increases with the increase of ionic liquid content. This is because the self-healing performance of the system has a significant component dependence; the self-healing efficiency of the material is significantly positively correlated with the amount of ionic liquid doping, that is, the higher the amount of ionic liquid doping, the better the self-healing efficiency of the material. Figure b shows the electrical self-healing performance of the PASU-10IL sample in Example 1. At the moment the sample is completely cut off, the resistance jumps abruptly. This is because after the physical fracture of the sample, the internal conductive path is completely interrupted, which leads to a sharp increase in resistance. When the two fracture surfaces are precisely aligned and bonded, the sample resistance drops rapidly within 300ms, quickly recovering to the initial resistance level before the damage. Moreover, the resistance after repair is not significantly different from the initial value, and no significant residual resistance or signal drift phenomenon is observed, demonstrating excellent electrical reversible recovery capability.

[0088] Figure 8 The antibacterial properties and biocompatibility of the intrinsic self-healing polyurea-based conductive elastomer PASU-xIL prepared in Examples 1 to 3 are shown in Figure a. In Figure a, when the doping concentration of the ionic liquid reaches 20 wt%, after co-culturing the PASU-xIL composite material with two tested bacterial strains for 24 h, the relative inhibition rate against *Escherichia coli* (E. coli) reaches 99.3%, and the inhibition rate against *Staphylococcus aureus* (S. aureus) reaches 99.1%, achieving near-complete eradication of these two common pathogenic bacteria, fully demonstrating excellent broad-spectrum antibacterial properties (Figure b). Figure c shows the relative cell viability of human skin fibroblasts after incubation in the PASU-10IL composite material extract for 24 h at concentrations of 6.25 mg / mL and 12.25 mg / mL, with no statistically significant difference compared to the blank control group. This indicates that the PASU-10IL composite material has no significant cytotoxicity and possesses good in vitro cell compatibility, providing reliable biosafety assurance for its long-term safe application in the field of wearable skin physiological signal sensing.

[0089] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A method for preparing an intrinsically self-healing polyurea-based conductive elastomer, characterized in that, Includes the following steps: (1) Synthesis of intrinsic self-healing polyurea elastomer (PASU): Polypropylene glycol bis(2-aminopropyl ether) and isocyanate monomers were dissolved in organic solvents. Under a dry nitrogen atmosphere at room temperature, the isocyanate monomer solution was added dropwise to the polypropylene glycol bis(2-aminopropyl ether) solution, and the polymerization reaction was carried out with continuous stirring at room temperature. Subsequently, 4,4'-diaminodiphenyl disulfide and 1,4-cyclohexanedimethylamine were added to the system, and the reaction was continued with stirring to carry out chain extension. After the reaction was completed, the solution was cast and dried to obtain a self-healing polyurea elastomer containing dynamic disulfide bonds. (2) Synthesis of self-healing polyurea-based conductive elastomer (PASU-xIL): The self-healing polyurea elastomer containing dynamic disulfide bonds was dissolved in an organic solvent, and then an ionic liquid was added. The mixture was stirred and mixed evenly at room temperature and under a dry nitrogen atmosphere. After solution casting and drying, the intrinsic self-healing polyurea-based conductive elastomer was obtained.

2. The method for preparing an intrinsically self-healing polyurea-based conductive elastomer according to claim 1, characterized in that, The amount of ionic liquid added is 5 wt% to 40 wt% of the mass of the self-healing polyurea elastomer containing dynamic disulfide bonds.

3. The method for preparing an intrinsically self-healing polyurea-based conductive elastomer according to claim 1, characterized in that, The polymerization reaction is carried out at room temperature under a dry nitrogen atmosphere for 4 to 12 hours; the chain extension reaction is carried out at room temperature under a dry nitrogen atmosphere for 0.5 to 2 hours.

4. The method for preparing an intrinsically self-healing polyurea-based conductive elastomer according to claim 1, characterized in that, The molar ratio of the isocyanate monomer, polypropylene glycol bis(2-aminopropyl ether), 4,4'-diaminodiphenyl disulfide and 1,4-cyclohexanedimethylamine is (1.5-2.5):(0.8-1.2):(0.3-0.8):(0.3-0.8).

5. A method for preparing an intrinsically self-healing polyurea-based conductive elastomer according to claim 1 or 4, characterized in that, The number-average molecular weight of the polypropylene glycol bis(2-aminopropyl ether) is 400–2000 g·mol⁻¹. -1 .

6. The method for preparing an intrinsically self-healing polyurea-based conductive elastomer according to claim 1, characterized in that, The isocyanate monomer is isophorone diisocyanate; the ionic liquid is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.

7. A method for preparing an intrinsically self-healing polyurea-based conductive elastomer according to claim 1 or 4, characterized in that, The molar ratio of the cis to trans isomers of the 1,4-cyclohexanedimethylamine is (65:35) to (85:15).

8. The method for preparing an intrinsically self-healing polyurea-based conductive elastomer according to claim 1, characterized in that, The organic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, or N-methylpyrrolidone.

9. An intrinsically self-healing polyurea-based conductive elastomer, characterized in that, The conductive elastomer obtained by the preparation method according to any one of claims 1-8.

10. An application of an intrinsically self-healing polyurea-based conductive elastomer, characterized in that, The conductive elastomer as described in any one of claims 9 is used to prepare flexible wearable sensors, human motion monitoring devices, or health monitoring devices.